2015
DOI: 10.1021/acs.chemmater.5b04250
|View full text |Cite
|
Sign up to set email alerts
|

Resolving the Structure of Ti3C2Tx MXenes through Multilevel Structural Modeling of the Atomic Pair Distribution Function

Abstract: MXenes are a recently discovered family of two-dimensional (2D) early transition metal carbides and carbonitrides, which have already shown many attractive properties and great promise in energy storage and many other applications. However, a complex surface chemistry and small coherence length have been obstacles in some applications of MXenes, also limiting the accuracy of predictions of their properties. In this study, we describe and benchmark a novel way of modeling layered materials with real interfaces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
338
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 414 publications
(359 citation statements)
references
References 61 publications
16
338
0
Order By: Relevance
“…The experimental measurements and theoretical predictions are not always consistent, as the MXene surfaces are covered by a random distribution of surface groups and intercalants which makes prediction of properties difficult. This has been observed by the few atomic resolution experiments reported so far, such as Paper III, Paper IV, Wang et al [123], and Wang et al [127].…”
Section: Propertiessupporting
confidence: 65%
See 4 more Smart Citations
“…The experimental measurements and theoretical predictions are not always consistent, as the MXene surfaces are covered by a random distribution of surface groups and intercalants which makes prediction of properties difficult. This has been observed by the few atomic resolution experiments reported so far, such as Paper III, Paper IV, Wang et al [123], and Wang et al [127].…”
Section: Propertiessupporting
confidence: 65%
“…Following studies assumed a full coverage of a single type of surface group (fluorine, oxygen, or hydroxide) and defect free MXenes, which predicted many MXenes as semiconductors with varying direct or indirect band gaps [114,118,124,134,135,136,137,138]. Recently, a study assuming a random distribution of surface groups has been performed, and showed results in good correlation with measurements [123].…”
Section: Propertiesmentioning
confidence: 98%
See 3 more Smart Citations